Manufacturing method of hollow particles, manufacturing method of hollow fibers

The method addresses the challenges of shape stability and manufacturing efficiency in producing hollow particles and fibers by using a specific solvent combination and spraying technique, resulting in high-yield, spherical, and smooth products.

JP7656459B2Active Publication Date: 2025-04-03FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021052997
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-04-03
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing methods for producing hollow particles and fibers using cellulose acetate face challenges in shape stability and manufacturing efficiency, particularly in achieving spherical hollow shapes and smooth surfaces.

Method used

A method involving a solution of triacetylcellulose, a good solvent, and a poor solvent, with specific volume ratios and solvent combinations, is sprayed to form hollow particles and fibers with stable spherical shapes and smooth surfaces.

Benefits of technology

The method enables the efficient production of hollow particles and fibers with high yield rates of spherical hollow shapes and smooth surfaces, improving manufacturing efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656459000001
    Figure 0007656459000001
  • Figure 0007656459000002
    Figure 0007656459000002
Patent Text Reader

Abstract

To provide a manufacturing method of hollow particles capable of simply manufacturing hollow particles that contain triacetyl cellulose and are held into a spherical hollow shape and a manufacturing method of hollow fibers capable of simply manufacturing hollow fibers containing triacetyl cellulose and having a smooth surface.SOLUTION: A manufacturing method of hollow particles comprises: a step A1 of preparing a solution containing triacetyl cellulose, a good solvent, and a poor solvent, wherein a volume ratio of a content of the poor solvent to a total content of the good solvent and the poor solvent is 5 to 30 vol.%; and a step A2 for spraying the solution to form hollow particles having an outer shell containing triacetyl cellulose, as well as, a manufacturing method of hollow fibers comprising; a step B1 of preparing a solution containing triacetyl cellulose, a good solvent and a poor solvent in which a volume ratio of a poor solvent content to a total content of the good solvent and the poor solvent, is 5 to 50% by volume; and a step B2 of ejecting the solution from a nozzle to form hollow fibers having an outer shell containing triacetyl cellulose.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing hollow particles and a method for producing hollow fibers. [Background technology]

[0002] Microplastics, which are particles or fibers formed using synthetic polymers, are used in a wide range of applications, such as cosmetic raw materials, resin additives, paints, abrasives, weight-reducing agents, and water and oil absorbents. On the other hand, in recent years, there are concerns that these microplastics are causing marine pollution, and that they may be ingested by aquatic organisms such as plankton and fish, and ultimately migrate into the human body. As a result, there are moves in various countries, including Japan, to restrict the use of synthetic polymers and plastics.

[0003] In light of the above, attempts are being made to expand the use of materials that have the property of being biodegradable in the natural environment (in soil, fresh water, and seawater). Representative biodegradable resins include cellulose acetates such as triacetyl cellulose (TAC). For example, Patent Document 1 describes a method for producing microspherical particles from a solution of a cellulose fatty acid ester by a spray drying method, in which a specific mixed solvent is used as a solvent for the solution. Patent Document 2 describes a method for producing a cellulose acetate tow band, which includes the steps of dissolving cellulose acetate having a calcium content of 20 ppm or less and a magnesium content of 30 ppm or more to prepare a spinning dope, filtering the spinning dope, and spinning cellulose acetate using the filtered spinning dope, in which no titanium oxide is added before the spinning step (see claim 6). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 60-023773 [Patent Document 2] JP 2020-007686 A Summary of the Invention [Problem to be solved by the invention]

[0005] With reference to the above patent documents, the inventors attempted to manufacture a component having a hollow structure with a cavity formed inside using cellulose acetate, and found that there was room for improvement in the shape stability and manufacturing efficiency of the component having a hollow structure, depending on the type of cellulose acetate and solvent.

[0006] In view of the above-mentioned circumstances, an object of the present invention is to provide a method for producing hollow particles that contains triacetyl cellulose and that can easily produce hollow particles that maintain a spherical hollow shape. Another object of the present invention is to provide a method for producing a hollow fiber that contains triacetyl cellulose and has a smooth surface, by which the hollow fiber can be easily produced. [Means for solving the problem]

[0007] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by the following configuration.

[0008] [1] A method for producing hollow particles, comprising: a step A1 of preparing a solution containing triacetyl cellulose, a good solvent, and a poor solvent, the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent being 5 to 30 volume %, and a step A2 of spraying the solution to form hollow particles having an outer shell containing triacetyl cellulose. [2] A method for producing a hollow fiber, comprising: a step B1 of preparing a solution containing triacetyl cellulose, a good solvent, and a poor solvent, in which the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is more than 10 volume % and not more than 30 volume %, and a step B2 of ejecting the solution from a nozzle to form a hollow fiber having an outer shell containing triacetyl cellulose. [3] The method according to [1] or [2], wherein the difference between the saturated vapor pressure of the good solvent at 20°C and the saturated vapor pressure of the poor solvent at 20°C is 35 kPa or more. [4] The distance between the Hansen solubility parameters of the good solvent and the poor solvent is 11.3 MPa. 1 / 2 The manufacturing method according to any one of [1] to [3], which is as follows: [5] The method according to any one of [1] to [4], wherein the good solvent comprises dichloromethane. [6] The method according to any one of [1] to [5], wherein the poor solvent comprises at least one selected from the group consisting of N-methyl-2-pyrrolidone and dimethylformamide. [7] The manufacturing method according to [1], wherein in the step A2, a ratio Q / V of a spray amount Q (L / min) of the solution sprayed in the step A2 to a flow rate V (L / min) of a dry air stream flowing in a direction in which the solution is sprayed is 0.1 or less. [8] The manufacturing method according to [1] or [7], wherein in step A2, the droplets formed by spraying the solution have a diameter of 1000 μm or less. [9] The manufacturing method according to [2], wherein in the step B2, a ratio Q2 / V of the discharge amount Q2 (L / min) of the solution discharged in the step B2 to a flow rate V (L / min) of the dry air flow flowing in the direction in which the solution is discharged is 0.1 or less.

[10] The manufacturing method according to [2] or [9], wherein in step B2, the diameter of the liquid flow formed by ejecting the solution is 1000 μm or less. Effect of the Invention

[0009] According to the present invention, there is provided a method for producing hollow particles, which can easily produce hollow particles that contain triacetyl cellulose and maintain a spherical hollow shape. Furthermore, according to the present invention, there can be provided a method for producing a hollow fiber that contains triacetyl cellulose and has a smooth surface, with ease. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In this specification, when two or more types of a component are present, the "content" of the component means the total content of those two or more components. In this specification, the "saturated vapor pressure" of a certain component means the saturated vapor pressure (unit: kPa) of that component at 20°C.

[0011] [First embodiment] The first embodiment of the present invention is a method for producing hollow particles, comprising step A1 of preparing a solution containing a combination of triacetyl cellulose (hereinafter also referred to as "TAC") and a specific solvent, and step A2 of spraying the obtained solution to form hollow particles having an outer shell containing TAC. The solution (hereinafter also referred to as "dope") used in the production of hollow particles in this embodiment contains TAC, a good solvent, and a poor solvent, and the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is 5 to 30 volume %.

[0012] The present inventors have intensively investigated a method for producing hollow particles containing cellulose acetate, and as a result, have found that, as described above, by spraying a dope containing a combination of TAC and a specific solvent and granulating it, hollow particles having a hollow structure in which the cavities are covered with an outer shell containing TAC, and in which the hollow structure maintains its spherical shape, can be simply produced. Although the reason why the above-mentioned hollow particles can be easily produced is not clear in detail, the present inventors speculate as follows. That is, when particles are formed from droplets of a solution containing cellulose acetate, the solvent evaporates rapidly from the outer periphery of the droplets to form a skin layer mainly composed of cellulose acetate, and then the solvent inside the skin layer evaporates and the skin layer collapses, resulting in the formation of particles with many wrinkles on the surface, which is presumably difficult to form hollow particles with a cross-sectional shape close to a circle. On the other hand, when a dope obtained by dissolving TAC in a mixed solution containing a good solvent and a poor solvent is sprayed and granulated, the rate of formation of the skin layer accompanying the evaporation of the solvent during the drying of the droplets is suppressed, and the formation time is delayed, so that a stronger skin layer can be formed, and as a result, hollow particles with a more stable spherical hollow shape can be produced.

[0013] In this embodiment, the phrase "maintains a hollow shape" or "has a hollow structure" means that the ratio of the total area of ​​cavities to the total cross-sectional area of ​​the particle, as measured by the method described below, is 10% or more. In addition, in this embodiment, the term "spherical" with respect to particles means that the sphericity of the particles, as measured by the method described below, is 0.5 or more. The method for producing hollow particles according to this embodiment will be described in detail below.

[0014] [Process A1] Step A1 in this embodiment is a step of preparing a solution (dope) containing TAC, a good solvent, and a poor solvent. An example of step A1 is a step of putting TAC, a good solvent, and a poor solvent into a container and then mixing them.

[0015] In step A1, the procedure for feeding the above components into the container is not particularly limited. For example, the above components may be fed all at once or each component may be fed sequentially from the feed opening of the container. In addition, when feeding one component, it may be fed in several batches. When each component is added sequentially, the order of addition is not particularly limited, but it is preferable to add the good solvent first, and then add the remaining components sequentially or all at once. When adding TAC to the container, a solution in which TAC has been dissolved in a good solvent in advance may be added.

[0016] In step A1, the mixture contained in the container is preferably stirred by a stirring means to prepare a dope in which each component is uniformly mixed. The stirring method is not particularly limited, and it is preferable to set the stirring means and stirring conditions so that the mixture is sufficiently stirred and the concentration of each component becomes uniform. The temperature of the mixture when carrying out the above mixing step is not particularly limited, but is preferably 15 to 40°C. The mixing time in the above mixing step is not particularly limited, but is preferably 1 to 24 hours in terms of the balance between the uniformity of the resulting dope and the productivity.

[0017] Each component contained in the dope prepared in step A1 will be described.

[0018] <Triacetyl cellulose (TAC)> In this embodiment, "triacetyl cellulose (TAC)" refers to a cellulose acylate in which the hydrogen atoms constituting the hydroxyl groups of cellulose, i.e., the free hydroxyl groups at the 2nd, 3rd and 6th positions of the β-1,4-bonded glucose units, are replaced with acetyl groups, and the degree of substitution of the acetyl groups is 2.6 or more. Here, the "substitution degree" refers to the degree of substitution of acetyl groups for hydrogen atoms constituting hydroxyl groups of cellulose. 13 It can be calculated by comparing the area intensity ratio of carbon of cellulose acylate measured by C-NMR method. Furthermore, TAC is a material that constitutes the outer shell of the hollow particles produced according to this embodiment.

[0019] The degree of substitution of the TAC used in this embodiment is preferably 2.6 to 2.9, and more preferably 2.8 to 2.9, in that it can achieve both water absorbency and quick drying properties and also has superior biodegradability. The degree of substitution of TAC can be appropriately adjusted by known methods such as changing the partial hydrolysis time during synthesis of TAC and alkaline saponification.

[0020] The weight average molecular weight (Mw) of TAC is not particularly limited, but from the viewpoint of the mechanical strength of the hollow particles, it is preferably 100,000 or more, and more preferably 100,000 to 500,000. The dispersity, which is the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the TAC, is preferably from 1.0 to 5.0, and more preferably from 1.0 to 4.0. In this specification, the weight average molecular weight and number average molecular weight are molecular weights measured by gel permeation chromatography (GPC).

[0021] TAC can be produced by a known method for producing cellulose acetate. For example, the so-called acetic acid method uses acetic anhydride as an acetylating agent, acetic acid as a diluent, and sulfuric acid as a catalyst. The basic steps of the acetic acid method are: (1) a pretreatment step in which a pulp raw material (dissolving pulp) having a relatively high α-cellulose content is disintegrated and crushed, and then acetic acid is sprayed and mixed; (2) an acetylation step in which the pretreated pulp of (1) is reacted with a mixed acid consisting of acetic anhydride, acetic acid, and an acetylation catalyst (e.g., sulfuric acid); (3) an aging step in which cellulose acetate is hydrolyzed to cellulose acetate having a desired acetylation degree; and (4) a posttreatment step in which the cellulose acetate after the hydrolysis reaction is precipitated from the reaction solution, purified, stabilized, and dried. For the raw materials and manufacturing method of TAC, see pages 7 to 12 of the Japan Institute of Invention and Innovation's Technical Bulletin (Technical Publication No. 2001-1745, published on March 15, 2001, Japan Institute of Invention and Innovation), the disclosure of which is incorporated herein by reference.

[0022] The content of TAC is not particularly limited, but in terms of better sprayability, the content of TAC (solid content concentration) relative to the total mass of the dope is preferably 1 to 5 mass%, more preferably 1 to 3 mass%.

[0023] <Solvent> The dope prepared in the step A1 of the present embodiment contains a good solvent and a poor solvent as the solvent. Here, a "good solvent" means a solvent that dissolves 1 g or more of TAC per liter of solvent at 25° C., and a "poor solvent" means a solvent that dissolves less than 1 g of TAC per liter of solvent at 25° C.

[0024] The good solvent can be used without any particular limitation as long as it satisfies the above-mentioned requirements for a good solvent. Examples of good solvents include dichloromethane, chloroform, acetone, methyl acetate, and ethyl acetate, with dichloromethane being preferred. The good solvent may be used alone or in combination of two or more kinds.

[0025] The poor solvent can be used without any particular limitation as long as it satisfies the above-mentioned requirements for a poor solvent. Examples of poor solvents include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), benzene, toluene, xylene, methanol, ethanol, 2-propanol, n-butanol, cyclohexane, and water. Of these, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), benzene, toluene, or xylene is preferred, and N-methyl-2-pyrrolidone (NMP) or dimethylformamide (DMF) is more preferred. The poor solvent may be used alone or in combination of two or more kinds.

[0026] The dope prepared in step A1 of the present embodiment has a volume ratio of the poor solvent content to the total content of the good solvent and the poor solvent of 5 to 30% by volume. By including the poor solvent in the dope in this range, the formation of a thin skin layer and the generation of wrinkles in the skin layer due to the rapid drying of the solvent in the subsequent step A2 can be suppressed, and as a result, particles having a hollow structure and maintaining the hollow structure in a spherical shape can be easily produced. In order to facilitate the production of hollow particles that maintain a spherical hollow shape, the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is preferably 10 to 25 volume %, more preferably 15 to 20 volume %.

[0027] The content of the solvent is not particularly limited, but is preferably 95 to 99% by mass, more preferably 97 to 99% by mass, based on the total mass of the dope. The solvent is preferably the remainder of the dope other than TAC.

[0028] As a combination of a good solvent and a poor solvent, a combination in which the difference obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent is 23 kPa or more is preferable, a combination in which the difference is 35 kPa or more is more preferable, and a combination in which the difference is 40 kPa or more is even more preferable. By setting the difference in saturated vapor pressure between the good solvent and the poor solvent within the above range, the dissolving function of the good solvent, which dissolves TAC and has a low saturated vapor pressure, and the function of the poor solvent, which suppresses and delays the formation of a skin layer during the drying process after spraying, are more effectively exhibited, thereby suppressing shrinkage of the skin layer in the later stage of the drying process and enabling the stable formation of hollow particles that maintain a spherical hollow shape. The upper limit of the difference is not particularly limited, but is, for example, 60 kPa or less, preferably 55 kPa or less, and more preferably 48 kPa or less.

[0029] For example, when the good solvent is dichloromethane (saturated vapor pressure: 47.4 kPa), poor solvents having a difference in saturated vapor pressure within the above-mentioned preferred range include NMP (saturated vapor pressure: 0.032 kPa), DMF (saturated vapor pressure: 0.35 kPa), water (saturated vapor pressure: 2.3 kPa), and toluene (saturated vapor pressure: 2.2 kPa).

[0030] For example, when the dope contains two or more good solvents, the saturated vapor pressure of each good solvent is converted by the mass of each good solvent contained in the dope, and the average value is used as the saturated vapor pressure of the whole good solvents, and the difference is calculated. The same applies when the dope contains two or more poor solvents.

[0031] In addition, as for the combination of a good solvent and a poor solvent, the distance between the Hansen solubility parameter of the good solvent and the Hansen solubility parameter of the poor solvent is 15.0 MPa 1 / 2 The following combination is preferable, and the above distance is 11.3 MPa. 1 / 2 A combination such that the distance is 3.0 MPa or less is more preferable. 1 / 2 More preferably, the distance is 1.7 MPa. 1 / 2 The following combinations are particularly preferred: By setting the SP value distance between the good solvent and the poor solvent within the above range, the solubility between the good solvent and the poor solvent is improved, and it is possible to more easily control the drying rate of the solvent from the droplets sprayed in step A2 and to more easily suppress the formation of a skin layer. From this viewpoint, it is preferable that the TAC-containing solution prepared in step A1 is not phase-separated. The lower limit of the above distance is not particularly limited, and is 0 MPa 1 / 2 It may be more than that.

[0032] In this specification, "Hansen Solubility Parameter" and "SP value" refer to the solubility parameters described in "Hansen Solubility Parameters: A User's Handbook, Second Edition, CMHansen (2007), Taylor and Francis Group, LLC (HSPiP Manual)" and the like, and are values ​​calculated by the following formula using "Practical Hansen Solubility Parameters HSPiP 3rd Edition" (software version 5.1.08) (unit: MPa 1 / 2 ). (SP value) 2 =(δd) 2 +(δp) 2 +(δh) 2 The Hansen solubility parameters express solubility as a multidimensional vector (dispersion term (δd), polarization term (δp), and hydrogen bond term (δh)), and these three parameters can be thought of as the coordinates of a point in a three-dimensional space called the Hansen space. The distance between the Hansen solubility parameters of a good solvent and a poor solvent means the distance between the good solvent and the poor solvent in the Hansen space, and is calculated by the following formula from the dispersion term (δd1), polarization term (δp1), and hydrogen bond term (δh1) of the good solvent, and the dispersion term (δd2), polarization term (δp2), and hydrogen bond term (δh2) of the poor solvent (unit: MPa) 1 / 2 ). (distance)={(δd1-δd2) 2 +(δp1-δp2) 2 +(δh1-δh2) 2} 1 / 2

[0033] For example, when the good solvent is dichloromethane, examples of poor solvents that bring the SP value distance into the above-mentioned preferred range include NMP, DMF, and toluene. For example, when the dope contains two or more good solvents, the center of gravity in the Hansen space is calculated from the SP value of each good solvent and the mass content in the dope, and the SP value of the center of gravity of the good solvent is used to calculate the distance from the SP value of the poor solvent. The same applies when the dope contains two or more poor solvents, and when there are two or more good solvents and two or more poor solvents, the distance between the centers of gravity is the distance between the SP values ​​of the good solvent and the poor solvent.

[0034] <Other ingredients> The dope may contain other components in addition to TAC, the good solvent and the poor solvent, so long as they do not inhibit the formation of hollow particles. Examples of the other components include cellulose acylates other than TAC. Here, "cellulose acylate" refers to a cellulose ester in which some or all of the hydrogen atoms constituting the hydroxyl groups of cellulose, i.e., the free hydroxyl groups at the 2nd, 3rd and 6th positions of β-1,4-bonded glucose units, are substituted with acyl groups. The degree of substitution of acyl groups in cellulose acylate other than TAC (hereinafter also referred to as "degree of acylation") is preferably 2.6 or more, more preferably 2.6 to 2.9.

[0035] Examples of the acyl group include an acetyl group (provided that the degree of substitution of the acetyl group is less than 2.6), a propionyl group, and a butyryl group. The acyl group substituted in the cellulose acylate other than TAC may be of one type alone or of two or more types in combination.

[0036] When the dope contains a cellulose acylate other than TAC, the total content of TAC and the cellulose acylate other than TAC is preferably within the above solid content range.

[0037] The dope preferably does not substantially contain any other components than TAC, good solvent, and poor solvent. More specifically, the content of the other components than TAC, good solvent, and poor solvent is preferably 1% by mass or less based on the total mass of the dope. The lower limit is not particularly limited, and may be 0% by mass based on the total mass of the dope.

[0038] The viscosity of the dope used in this step can be appropriately selected depending on the production conditions of step A2 (e.g., the method of spraying the dope, the shape of the nozzle used for spraying, and the particle diameter of the desired hollow particles), but the viscosity of the dope at 25°C is preferably 10 to 1000 mPa s.

[0039] [Process A2] Step A2 in this embodiment is a step of spraying a solution (dope) containing TAC, a good solvent, and a poor solvent to form hollow particles having an outer shell containing TAC.

[0040] The method of spraying the dope in step A2 is not particularly limited as long as it is a known method for forming minute droplets of the dope and drying the formed droplets, and examples thereof include a spray-drying method, a freeze-spray-drying method, a vacuum spray-drying method, and a liquid- or submerged spraying method in which droplets are sprayed from a solidifying solvent or gas into the solidifying solvent. Among them, the spray-drying method is preferred.

[0041] The spray-drying method is a method in which the dope is sprayed using an atomizer, and the resulting fine droplets are dried in a heated dry air stream to form particles. The sprayer used for spraying the dope may be a known sprayer such as a two-fluid nozzle, a one-fluid nozzle, or a disk rotary type. It is preferable to use a sprayer with a narrow spray area and directionality in order to suppress adhesion of droplets to the inner wall of the drying chamber and to produce hollow particles with a more uniform particle size. Examples of such a sprayer include a sprayer equipped with a two-fluid nozzle and a one-fluid nozzle.

[0042] The dope supplied to the atomizer is sprayed, for example, in a drying chamber in which a heated dry air flow flows. The droplets formed by the spraying are dried by the dry air flow, and hollow particles having an outer shell containing TAC are formed as described above. The formed hollow particles are collected by known collection means such as a cyclone or a filter.

[0043] The temperature of the drying air stream is preferably 40 to 250° C., and more preferably 100 to 200° C. By setting the temperature within the above range, it is possible to improve the removal of the solvent and the retention of the hollow shape in a well-balanced manner. The amount of the dope supplied to the nozzle, that is, the amount of the dope sprayed from the nozzle, can be appropriately selected depending on the size and shape of the nozzle and the size of the drying chamber, and is, for example, 0.1 to 10 L / min.

[0044] In step A2, the diameter of the droplets formed by spraying the dope (droplet diameter) is preferably 2000 μm or less, more preferably 1000 μm or less. By setting the droplet diameter of the dope to be within the above range, the droplets can be dried more efficiently, and as a result, hollow particles having a hollow structure can be produced more easily. The lower limit of the droplet diameter is not particularly limited, and is, for example, 3 μm or more.

[0045] The direction of the dry air flow in the drying chamber may be a forward direction along the direction in which the dope is sprayed, a reverse direction opposite to the direction in which the dope is sprayed, or a direction intersecting the direction in which the dope is sprayed, but the forward direction is preferable. In step A2, the ratio Q / V of the spray amount Q (L / min) of the solution sprayed in step A2 to the flow rate V (L / min) of the dry airflow flowing in the direction in which the dope is sprayed in the drying chamber is preferably 0.5 or less, more preferably 0.1 or less. By providing a dry airflow of a predetermined amount or more relative to the total amount of droplets to be sprayed, the evaporated solvent can be diffused, the solvent concentration in the airflow can be maintained low, and the droplets can be dried efficiently. As a result, hollow particles that maintain a hollow structure can be produced more easily. The lower limit of the ratio Q / V is not particularly limited, and is, for example, 0.01 or more.

[0046] [Characteristics of hollow particles] By the manufacturing method of this embodiment including the above-mentioned steps A1 and A2, hollow particles having a hollow structure in which the cavities are covered with an outer shell containing TAC and which maintain a spherical hollow shape can be easily manufactured. That is, according to the manufacturing method of this embodiment, hollow particles that maintain a spherical hollow shape can be manufactured more efficiently. For example, although not limited to the following aspect, the ratio (yield) of the total number of hollow particles that maintain a spherical hollow shape to the total number of particles manufactured by the manufacturing method of this embodiment is preferably 50% or more, more preferably 80% or more. The upper limit is not particularly limited, and may be 100% or less.

[0047] Examples of hollow particles produced by the production method of this embodiment include hollow particles having the following characteristics. However, the hollow particles produced by the production method of this embodiment are not limited to those having the following characteristics.

[0048] The shell constituting the hollow particles preferably contains TAC and is substantially composed of TAC. More specifically, the content of TAC in the hollow particles is preferably 80% by mass or more, more preferably 90% by mass or more, based on the total mass of the hollow particles (equal to the total mass of the shell). The upper limit is not particularly limited, and may be 100% by mass based on the total mass of the hollow particles.

[0049] The thickness of the outer shell is not particularly limited and is, for example, 0.1 to 200 μm, preferably 10 to 50 μm. As described above, the hollow particles have cavities formed therein such that the ratio of the total area of ​​the cavities to the area surrounded by the outer periphery of the hollow particle in the cross section of the hollow particle (i.e., the total cross-sectional area) is 10% or more. The ratio in the hollow particles is preferably 10 to 80%, and more preferably 50 to 80%. The thickness of the shell and the size of the cavity formed inside the hollow particle can be measured from a cross-sectional image obtained by observing the cross section of the hollow particle using an electron microscope, as described in the Examples below. In the manufacturing method of the present embodiment, the thickness of the shell and the size of the cavity formed inside the hollow particle can be controlled by adjusting conditions such as the combination and content of the good solvent and the poor solvent, the solid content of the dope, the temperature of the drying airflow, the flow rate of the drying airflow, and the spray amount of the TAC solution.

[0050] The average particle size of the hollow particles is, for example, 1 to 2000 μm, preferably 10 to 1000 μm, and more preferably 10 to 500 μm. The average particle size of the hollow particles can be measured by the following method. The hollow particles are observed using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). At this time, the sample, observation conditions, and magnification are appropriately adjusted. At least 100 particles are randomly selected from the obtained observation image, the particle diameters of the selected particles are measured, and the obtained particle diameters are averaged to obtain the average particle diameter. The average particle size of the hollow particles can be controlled by, for example, the concentration of the dope to be sprayed, the spray pressure, the speed of the sprayed droplets, and other conditions.

[0051] The average sphericity of the hollow particles produced by the production method of this embodiment is preferably 0.5 or more, more preferably 0.7 or more. The upper limit of the average sphericity of the hollow particles is not particularly limited and may be 1.0 or less, but in practice it is often 0.9 or less. The average sphericity of hollow particles is determined by the following method. 100 hollow particles are randomly selected, and the cross-sectional shapes of the selected particles are observed using an electron microscope. From the cross-sectional images of the observed hollow particles, the sphericity of each particle is determined by the method described in the Examples below, and the average value of the obtained sphericities is calculated to obtain the average sphericity of the hollow particles. In the manufacturing method of the present embodiment, the average sphericity of the hollow particles can be controlled by adjusting conditions such as the combination and content of the good solvent and the poor solvent, the solid content of the dope, the temperature of the drying airflow, the flow rate of the drying airflow, and the spray amount of the TAC solution.

[0052] The hollow particles produced by the production method of this embodiment can be preferably used for, for example, cosmetic raw materials, resin additives, paints, abrasives, weight-reducing agents, and water and oil absorbents. The hollow particles produced by the production method of this embodiment can also be preferably used for plant culture media.

[0053] [Second embodiment] A second embodiment of the present invention is a method for producing a hollow fiber, comprising step B1 of preparing a solution containing a combination of TAC and a specific solvent, and step B2 of ejecting the resulting solution from a nozzle to form a hollow fiber having an outer shell containing TAC. In this embodiment, the solution (dope) used in the production of hollow fibers contains TAC, a good solvent, and a poor solvent, and the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is more than 10 volume % and 30 volume % or less.

[0054] The present inventors have conducted extensive research into a method for producing hollow fibers containing cellulose acetate, and have found that, as described above, hollow fibers having a cylindrical outer shell with a smooth surface can be easily produced by discharging a dope containing a combination of TAC and a specific solvent from a nozzle. Although the reason why the above-mentioned hollow fibers can be easily produced is not clear in detail, the inventors speculate that when the above-mentioned specific dope is discharged from a nozzle to produce hollow fibers as in the first embodiment, the rate of formation of a cylindrical skin layer caused by evaporation of the solvent during drying is suppressed, and the timing of the formation is delayed, so that a stronger skin layer can be formed, and as a result, hollow fibers having a smooth surface can be produced.

[0055] In this embodiment, the term "hollow fiber" refers to a fibrous or thread-like member (fiber) that extends in one direction and has a hollow structure. Furthermore, the fiber "having a hollow structure" means that the ratio of the total area of ​​cavities to the total cross-sectional area in a cross section perpendicular to the longitudinal direction of the fiber, measured by the method described below, is 10% or more. Furthermore, with regard to a hollow fiber (or fiber), "having a smooth surface" means that the shape of the cross section perpendicular to the longitudinal direction of the hollow fiber (hereinafter also simply referred to as the "cross-sectional shape of the hollow fiber") is nearly circular and has few wrinkles in the circumferential direction of the outer periphery; more specifically, this means that the circularity of the cross-sectional shape of the hollow fiber, as measured by the method described below, is 0.5 or more. The method for producing a hollow fiber according to this embodiment will be described in detail below.

[0056] [Process B1] Step B1 in this embodiment is a step of preparing a solution (dope) containing TAC, a good solvent, and a poor solvent. The method for preparing the dope in step B1 and each component contained in the dope are the same as those in step A1 of the first embodiment, including the preferred aspects, except for the following points, so the description will be omitted.

[0057] The dope prepared in step B1 of the present embodiment has a volume ratio of the poor solvent content to the total content of the good solvent and the poor solvent of more than 10 volume % and not more than 30 volume %. By including the poor solvent in the dope in this range, the formation of a thin skin layer and the occurrence of wrinkles in the skin layer due to rapid drying of the solvent in the subsequent step B2 can be suppressed, and as a result, hollow fibers with a smooth surface can be easily produced. In order to facilitate the production of hollow fibers having a smooth surface, the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent is preferably more than 10 volume % and 25 volume % or less, and more preferably 15 to 20 volume %.

[0058] The content of TAC in the dope used in step B1 is not particularly limited, but the content (solid content concentration) of TAC relative to the total mass of the dope is preferably 6 to 23 mass%, more preferably 6 to 15 mass%, in order to prevent the liquid column from being broken by the surface tension of the liquid during extrusion and to enable a stable fiber shape to be formed. When the solid content concentration of the dope is equal to or less than the upper limit, the rapid formation of a TAC skin layer and the subsequent deformation due to drying shrinkage are further suppressed, and hollow fibers with a smooth surface can be more easily produced. The content of the solvent is not particularly limited, but is preferably 77 to 94% by mass, more preferably 85 to 94% by mass, based on the total mass of the dope. The solvent is preferably the remainder of the dope other than TAC. The viscosity of the dope used in step B1 can be appropriately selected depending on the production conditions in step B2 (e.g., the shape of the nozzle and the desired thickness of the hollow fiber), but it is preferable that the viscosity of the dope at 25°C is more than 1000 mPa·s and not more than 10,000 mPa·s.

[0059] [Process B2] Step B2 in this embodiment is a step of discharging a solution (dope) containing TAC, a good solvent, and a poor solvent from a nozzle to form a hollow fiber having a cylindrical outer shell containing TAC.

[0060] The method for discharging the dope in step B2 is not particularly limited as long as it is a known method for discharging the dope from a discharging means such as a nozzle. For example, the dope is supplied to a nozzle by a supplying means such as a pump, and the dope is discharged from the nozzle into a drying chamber. The nozzle used in the step B2 is not particularly limited as long as it has a flow path for discharging the dope, and examples thereof include a two-fluid nozzle and a one-fluid nozzle. The diameter of the nozzle outlet through which the dope is discharged is, for example, 0.01 to 2 mm, and preferably 0.04 to 0.5 mm.

[0061] The dope discharged from the nozzle into the drying chamber becomes a filamentous liquid flow and flows down in the drying chamber to be dried. In the drying chamber, a dry air flow is preferably flowing to accelerate the drying, and a heated dry air flow is more preferably flowing. The liquid flow is dried by the dry air flow, and the good solvent and the poor solvent are evaporated, resulting in a hollow fiber having a cylindrical shell containing TAC. The formed hollow fibers are collected by a known collecting means such as a winding and collecting device inside or outside the drying chamber.

[0062] The temperature of the drying air stream is preferably 40 to 250° C., and more preferably 100 to 200° C. By setting the temperature within the above range, removal of the solvent and formation of hollow fibers having a smooth surface can be achieved in a well-balanced manner. The amount of the dope supplied to the nozzle, that is, the amount of the dope discharged from the nozzle, can be appropriately selected depending on the size and shape of the nozzle and the size of the drying chamber, and is, for example, 0.3 to 1 L / min.

[0063] In step B2, the thickness (liquid flow diameter) of the liquid flow formed by the discharge of the dope is preferably 2000 μm or less, more preferably 1000 μm or less. By setting the liquid flow diameter of the discharged dope to be within the above range, the liquid flow can be dried more efficiently, and as a result, hollow fibers having a smooth surface can be produced more easily. The lower limit of the liquid flow diameter is not particularly limited, but is preferably 10 μm or more in terms of being able to further suppress deformation due to drying shrinkage accompanying rapid evaporation of the solvent.

[0064] The direction of the dry air flow in the drying chamber may be a forward direction along the direction in which the dope is discharged, a reverse direction opposite to the direction in which the dope is discharged, or a direction intersecting the direction in which the dope is discharged, but the forward direction is preferable. In step B2, the ratio Q2 / V of the discharge amount Q2 (L / min) of the solution discharged in step A2 to the flow rate V (L / min) of the dry airflow flowing in the direction in which the dope is discharged in the drying chamber is preferably 0.5 or less, more preferably 0.1 or less. By providing a predetermined amount of dry airflow to the total amount of the discharged liquid flow, the evaporated solvent can be diffused, the solvent concentration in the airflow can be kept low, and the liquid flow can be dried efficiently. As a result, hollow fibers having a smooth surface can be produced more easily. The lower limit of the ratio Q2 / V is not particularly limited, and is, for example, 0.01 or more.

[0065] [Characteristics of hollow fibers] According to the production method of this embodiment including the above-mentioned steps B1 and B2, a hollow fiber having a hollow structure in which the cavity is covered with a cylindrical outer shell containing TAC and a smooth surface can be easily produced. That is, according to the production method of this embodiment, hollow fibers having a smooth surface can be produced more efficiently. For example, although not limited to the following aspect, the ratio (yield) of the total number of hollow fibers having a smooth surface to the total number of hollow fibers produced by the production method of this embodiment is preferably 50% or more, and more preferably 80% or more. There is no particular upper limit to the yield, and it may be 100% or less.

[0066] Manufactured. Examples of hollow fibers produced by the production method of the present embodiment include hollow fibers having the following characteristics. However, the hollow fibers produced by the production method of the present embodiment are not limited to those having the following characteristics.

[0067] The shell constituting the hollow fiber preferably contains TAC and is substantially composed of TAC. More specifically, the content of TAC in the hollow fiber is preferably 80% by mass or more, more preferably 90% by mass or more, based on the total mass of the hollow fiber (equal to the total mass of the shell). There is no particular upper limit, and the content may be 100% by mass based on the total mass of the hollow fiber.

[0068] The average circularity of the hollow fibers produced by the production method of this embodiment is preferably 0.5 or more, and more preferably 0.7 or more. Furthermore, the upper limit of the circularity of the hollow fiber is not particularly limited and may be 1.0 or less, but in practice it is often 0.9 or less. The average value of the circularity of hollow fibers is obtained by the following method. 100 hollow fibers are randomly selected, and the cross-sectional shapes of the selected hollow fibers are observed using an electron microscope. From the cross-sectional images of the observed hollow fibers, the circularity of each hollow fiber is obtained by the method described in the Examples below, and the average value of the obtained circularities is calculated, thereby obtaining the average value of the circularity of the hollow fibers. In the production method of the present embodiment, the average circularity of the hollow fibers can be controlled by adjusting conditions such as the combination and contents of the good solvent and the poor solvent, the solids concentration of the dope, the temperature of the dry air stream, the flow rate of the dry air stream, and the discharge amount of the TAC solution.

[0069] The thickness of the outer shell is not particularly limited and is, for example, 0.1 to 200 μm, preferably 10 to 50 μm. As described above, the hollow fibers have cavities formed therein such that the ratio of the total area of ​​the cavities to the area surrounded by the periphery of the hollow fibers in the cross section of the hollow fibers (i.e., the total cross-sectional area) is 10% or more. The ratio in the hollow fibers is preferably 10 to 80%, and more preferably 50 to 80%. The thickness of the outer shell and the size of the cavity inside the hollow fiber can be measured from a cross-sectional image obtained by observing the cross-sectional shape of the hollow fiber using an electron microscope, as described in the Examples below. In the production method of the present embodiment, the thickness of the shell and the size of the cavity formed inside the hollow fiber can be controlled by adjusting conditions such as the combination and content of the good solvent and the poor solvent, the solids concentration of the dope, the temperature of the dry air stream, the flow rate of the dry air stream, and the discharge amount of the TAC solution.

[0070] The thickness of the hollow fiber is not particularly limited, and for example, the average outer diameter of the cross-sectional shape of the hollow fiber in a cross section perpendicular to the longitudinal direction of the hollow fiber is, for example, 1 to 2000 μm, preferably 10 to 1000 μm, and more preferably 10 to 500 μm. When the thickness of the hollow fiber is equal to or greater than the above lower limit, the specific surface area is not too small, so that deformation due to drying shrinkage accompanying rapid evaporation of the solvent during production can be suppressed, and hollow fibers with a smooth surface can be produced. The average outer diameter of the cross-sectional shape of a hollow fiber can be determined by randomly selecting at least 100 hollow fibers from a cross-sectional image obtained by observing the cross-sectional shape of the hollow fiber with an electron microscope, measuring the outer diameters of the selected hollow fibers, and calculating the arithmetic average of the obtained outer diameters. The thickness of the hollow fiber can be controlled by, for example, the solids concentration of the dope, the discharge pressure, the speed of the discharged liquid column, and other conditions.

[0071] The hollow fibers produced by the production method of this embodiment can be preferably used for applications such as water retention materials, weight-reducing agents, water and oil absorbing agents, etc. In addition, the hollow fibers produced by the production method of this embodiment can also be preferably used as plant culture media. EXAMPLES

[0072] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0073] [Example A: Production of hollow particles] Example A1 Triacetyl cellulose (TAC) (degree of substitution: 2.87) and a mixed solvent containing dichloromethane (good solvent) and N-methyl-2-pyrrolidone (NMP) (poor solvent) with a volume ratio of dichloromethane:NMP of 8:2 were placed in a container and stirred and mixed at room temperature (25°C) for 6 hours to obtain a TAC solution (dope). The content (solid concentration) of TAC relative to the total mass of the obtained solution was 2 mass%.

[0074] The TAC solution adjusted to 25°C was sprayed into dry air at 140°C using a spray dryer equipped with a two-fluid nozzle (B290 manufactured by Nippon Buchi Co., Ltd.) and dried to obtain hollow particles having an outer shell made of TAC. The average particle size of the obtained hollow particles was 100 μm. The amount of TAC solution sprayed from the two-fluid nozzle was 2.5 L / min, and the diameter of the droplets sprayed from the two-fluid nozzle was 500 μm. Dry air at 140° C. was sprayed from the other outlet of the two-fluid nozzle at a rate of 50 L / min. In addition, dry air was made to flow in the vicinity of the nozzle in the chamber of the spray dryer along the spray direction of the TAC solution. The flow rate V of this dry air flow in the chamber was 50 L / min. Therefore, the ratio Q / V of the spray amount Q (L / min) of the TAC solution sprayed from the nozzle to the flow rate V of the dry air flow flowing in the direction in which the TAC solution is sprayed was 0.05.

[0075] The diameter of droplets sprayed from the nozzle was measured by the following method. A drying container made of heat-resistant glass that transmits visible light was used as the chamber of the spray dryer, and the TAC solution was sprayed under the same conditions as above to produce hollow particles. The vicinity of the nozzle outlet was observed with a high-speed video camera ("speeder V2" manufactured by Photoron Co., Ltd.). 100 droplets were randomly selected from the obtained observation image, and the diameter of each droplet was measured, and the arithmetic average of the obtained measurements was taken as the droplet diameter.

[0076] [Examples A2 and A5] A TAC solution was prepared and hollow particles were produced (Example A2) according to the method described in Example A1, except that dimethylformamide (DMF) was used as the poor solvent instead of NMP. Moreover, a TAC solution was prepared in accordance with the method described in Example A1, except that methanol was used as the poor solvent instead of NMP, and hollow particles were produced (Example A5).

[0077] [Examples A3 and A8] A TAC solution was prepared and hollow particles were produced according to the method described in Example A1, except that the spray amount Q of the TAC solution and the flow rate V of the dry air stream were controlled so that the droplet diameter of the TAC solution sprayed from the nozzle was 1000 μm (Example A3). The average particle diameter of the obtained hollow particles was 200 μm. In addition, the TAC solution was prepared and hollow particles were produced according to the method described in Example A1, except that the spray amount Q of the TAC solution and the flow rate V of the dry air stream were controlled so that the droplet diameter of the TAC solution sprayed from the nozzle was 1200 μm (Example A8). The average particle diameter of the obtained hollow particles was 240 μm.

[0078] [Examples A4 and A7] A TAC solution was prepared and hollow particles were produced according to the method described in Example A1, except that the flow rate V of the dry air flowing in the chamber along the spraying direction of the TAC solution was changed to 25 L / min and the ratio Q / V was changed to 0.10 (Example A4). In addition, the flow rate V of the dry air flow flowing in the chamber along the spraying direction of the TAC solution was changed to 20 L / min, and the ratio Q / V was changed to 0.12. Except for this, the TAC solution was prepared according to the method described in Example A1, and hollow particles were produced (Example A7).

[0079] Example A6 A TAC solution was prepared and hollow particles were produced according to the method described in Example A1, except that water was used instead of NMP as a poor solvent and the mixing ratio of dichloromethane and water was changed so that the volume ratio of dichloromethane:water was 19:1.

[0080] [Example A9, Comparative Examples A1 to A3] A TAC solution was prepared and hollow particles were produced according to the method described in Example A1, except that the mixing ratio of dichloromethane and NMP was changed so that the volume ratio of the content of NMP to the total content of dichloromethane and NMP was the value shown in the "Solvent Ratio" column in Table 1 described later.

[0081] [Comparative example A4] Cellulose acetate propionate pellets and polyvinyl alcohol were mixed in a mass ratio of 10:90. The resulting mixture was fed into a twin-screw extruder and melt-kneaded at 250°C to produce an extruded dispersion. The resulting extruded dispersion was mixed with water and dissolved to produce particles with an average particle size of 100 μm.

[0082] 〔evaluation〕 The yield of particles produced in each of the Examples and Comparative Examples was measured by the following method. For each particle, 100 particles were randomly selected, and the cross-sectional shape of the selected particles was observed using an electron microscope. From the cross-sectional images of the observed particles, the sphericity of each particle was determined using the method described below, and the presence or absence of a hollow structure was confirmed. Here, if the sphericity of a particle is 0.5 or more, the particle is defined as spherical. The ratio of the number of particles that are spherical and have a hollow structure among the 100 selected particles (number of spherical and hollow particles / number of measured particles x 100) was defined as the yield (%), and the yield of the manufacturing methods of each Example and Comparative Example was evaluated based on the following evaluation criteria.

[0083] (Evaluation Criteria) A: The rate is 80% or more. B: Profitability is between 50% and 80% C: Profitability is 30% or more but less than 50% D: Profitability is less than 30%

[0084] The sphericity of a particle is determined by the following method. From the cross-sectional image of the particle, the projected area (A) and perimeter (M) of the particle are measured. If a perfect spherical cross section (a perfect circle) with a perimeter (M) is assumed, its radius (r) is M / 2π, and the cross-sectional area (B) of the assumed perfect sphere is π×(M / 2π). 2 The sphericity is calculated from the projected area (A) and the assumed cross-sectional area of ​​a sphere (B), A / B = 4π×A / M2. The sphericity of the particle is obtained by taking the arithmetic average of the sphericities of the selected 100 particles. The presence or absence of a hollow structure in the particles was confirmed by the following method: From the cross-sectional image of the above particle, the projected area (A) surrounded by the outer periphery of the above particle and the total area (P) of the cavities observed in the cross section were measured, and if the area ratio of the total area (P) of the cavities to the projected area (A) (total cross-sectional area of ​​the particle) was 10% or more, the particle was defined as a hollow particle having a hollow structure.

[0085] Table 1 below shows the composition of the dope used to prepare the particles, the spraying conditions for forming the particles, and the above evaluation results for the particle production methods of each of the Examples and Comparative Examples. In the table, the column "Solvent ratio" of "Solvent" indicates the content of the poor solvent relative to the total volume of the good solvent and the poor solvent (unit: volume %). In the table, the "SP value distance" column for "Solvent" indicates the distance between the SP value of a good solvent and the SP value of a poor solvent (unit: MPa 1 / 2 ) is shown. In the table, the "vapor pressure difference" column for "solvent" indicates the difference (unit: kPa) obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent. In the table, the "Q / V" column under "Spraying conditions" indicates the ratio of the spray amount Q (L / min) of the TAC solution sprayed from the nozzle to the flow rate V (L / min) of the dry airflow flowing in the direction in which the TAC solution is sprayed.

[0086] [Table 1]

[0087] As shown in Table 1, it was confirmed that the method for producing hollow particles according to the present invention makes it possible to easily produce hollow particles that contain triacetyl cellulose and maintain their hollow shape. In contrast, in Comparative Example A1, in which the volume ratio of the content of the poor solvent to the total volume of the good solvent and the poor solvent was less than 5 volume %, the yield of hollow particles having a spherical hollow structure was less than 50%. This is presumably because the content of the poor solvent was too small, causing the good solvent to evaporate rapidly from the sprayed droplets to form a TAC skin layer, and the skin layer to collapse due to the subsequent evaporation of the solvent, resulting in the formation of many non-spherical hollow particles having numerous wrinkles on the surface. In Comparative Examples A2 and A3, where the volume ratio of the poor solvent content to the total volume of the good solvent and poor solvent was more than 30 volume %, the yield of hollow particles having a spherical hollow structure was also less than 50%. This is presumably because the content of the poor solvent was too high, which slowed down the evaporation rate of the solvent from the droplets and made the layer composed of TAC thick, making it difficult to form cavities of a predetermined size inside the particles.

[0088] It was also confirmed that when the poor solvent contained NMP or DMF, the yield of hollow particles retaining their hollow shape was improved (comparison between Examples A1, A2, A5 and A6). It was also confirmed that when the difference obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent is 35 kPa or more, the yield of hollow particles retaining their hollow shape is further improved (comparison between Examples A1, A2, and A5).

[0089] It was also confirmed that when the droplet diameter of the TAC solution sprayed from the nozzle was 1000 μm or less, the yield of hollow particles that maintained their hollow shape was improved (comparison between Examples A3 and A8). In addition, it was confirmed that when the ratio Q / V of the spray amount Q (L / min) of the TAC solution sprayed from the nozzle to the flow rate V (L / min) of the dry airflow flowing in the direction in which the TAC solution is sprayed is 0.1 or less, the yield of hollow particles retaining their hollow shape is further improved (comparison between Examples A4 and A7).

[0090] [Example B: Production of hollow fibers] [Example B1] A TAC solution (dope) was discharged from the two-fluid nozzle of a spray dryer (B290, manufactured by Nippon Buchi Co., Ltd.) according to the method described in Example A1 above, except that a TAC solution was prepared and used in which the TAC content (solid content concentration) relative to the total mass of the solution was 6 mass%. As a result, hollow fibers having a cylindrical outer shell made of TAC were formed. The viscosity of the TAC solution used to prepare the hollow fibers was 2000 mPa s at 25°C. The thickness of the obtained hollow fibers (average outer diameter of the cross-sectional shape) was 100 μm. The discharge rate Q2 of the TAC solution from the nozzle was 2.5 L / min, and the cross-sectional diameter of the fluid discharged from the nozzle (liquid flow diameter) was 500 μm. Dry air at 140° C. was discharged from the other outlet of the two-fluid nozzle at a discharge rate of 50 L / min.

[0091] The diameter of the liquid flow of the TAC solution discharged from the nozzle was measured from an observation image obtained by a high-speed video camera ("speeder V2" manufactured by Photron Corporation) in accordance with the method for measuring the diameter of droplets sprayed from the nozzle in Example A above.

[0092] [Examples B2 and B5] A TAC solution was prepared and a hollow fiber was produced according to the method described in Example B1, except that DMF was used instead of NMP as the poor solvent (Example B2). Moreover, a TAC solution was prepared according to the method described in Example B1, except that methanol was used as the poor solvent instead of NMP, and a hollow fiber was produced (Example B5).

[0093] [Examples B3 and B7] A TAC solution was prepared according to the method described in Example B1, except that the discharge amount Q2 of the TAC solution and the flow rate V of the dry air stream were controlled so that the diameter of the TAC solution discharged from the nozzle was 1000 μm, and a hollow fiber was produced (Example B3). The diameter of the obtained hollow fiber was 200 μm. In addition, the TAC solution was prepared according to the method described in Example B1, except that the discharge amount Q2 of the TAC solution and the flow rate V of the dry air stream were controlled so that the liquid flow diameter of the TAC solution discharged from the nozzle was 1200 μm, and a hollow fiber was produced (Example B7). The thickness of the obtained hollow fiber was 240 μm.

[0094] [Examples B4 and B6] A TAC solution was prepared and a hollow fiber was produced according to the method described in Example B1, except that the flow rate V of the dry air flowing in the chamber along the discharge direction of the TAC solution was changed to 25 L / min and the ratio Q2 / V was changed to 0.10 (Example B4). In addition, the flow rate V of the dry air flowing in the chamber along the discharge direction of the TAC solution was changed to 20 L / min, and the ratio Q2 / V was changed to 0.12. Except for this, the TAC solution was prepared according to the method described in Example B1, and hollow fibers were produced (Example B6).

[0095] [Example B8, Comparative Examples B1 to B3] A TAC solution was prepared according to the method described in Example B1, except that the mixing ratio of dichloromethane and NMP was changed so that the volume ratio of the NMP content to the total content of dichloromethane and NMP was the value shown in the "Solvent Ratio" column in Table 2 described later, and the hollow fibers of Example B8 and Comparative Examples B1 to B3 were each produced.

[0096] 〔evaluation〕 The yield of the fibers produced in each of the Examples and Comparative Examples was measured by the following method. For each fiber, 100 fibers were randomly selected, and the cross-sectional shape of the selected fibers was observed using an electron microscope. From the cross-sectional images of the observed fibers, the circularity of the cross-sectional shape of each fiber was determined by the method described below, and the presence or absence of a hollow structure was confirmed. Here, when the circularity of the cross-sectional shape of a fiber is 0.5 or more, the fiber was defined as having a circular cross-sectional shape with a smooth surface. The ratio of the number of fibers with smooth circular surfaces among the 100 selected fibers (number of fibers with smooth circular surfaces / number of fibers measured x 100) was defined as the yield (%), and the yield of the manufacturing methods of each Example and Comparative Example was evaluated based on the following evaluation criteria.

[0097] (Evaluation Criteria) A: The rate is 80% or more. B: Profitability is between 50% and 80% C: Profitability is 30% or more but less than 50% D: Profitability is less than 30%

[0098] The circularity of the cross-sectional shape of the fiber is determined by the following method. From a cross-sectional image of the above-mentioned fiber in a cross section perpendicular to the longitudinal direction, the projected area (A) and perimeter (M) enclosed by the outer periphery of the fiber cross section are measured. If a perfect circle with perimeter (M) is assumed, the radius (r) of the perfect circle is M / 2π, and the area (B) of the assumed perfect circle is π × (M / 2π). 2 The circularity is calculated from the projected area (A) and the assumed circular area (B), A / B = 4π × A / M2. The circularity of the cross-sectional shape of the fiber is obtained by taking the arithmetic average of the circularities of the selected 100 fibers. The presence or absence of a hollow structure in the fiber was confirmed by the following method: From the cross-sectional image of the fiber, the projected area (A) surrounded by the outer periphery of the fiber cross section and the total area (P) of cavities observed in the cross section were measured, and if the area ratio of the total area (P) of cavities to the projected area (A) (total cross-sectional area of ​​the fiber) was 10% or more, the fiber was defined as a hollow fiber having a hollow structure.

[0099] Table 2 below shows the composition of the dope used to prepare the fiber, the discharge conditions for forming the fiber, and the results of the above evaluation for the fiber manufacturing methods of each Example and Comparative Example. In the table, the column "Solvent ratio" of "Solvent" indicates the content of the poor solvent relative to the total volume of the good solvent and the poor solvent (unit: volume %). In the table, the "SP value distance" column for "Solvent" indicates the distance between the SP value of a good solvent and the SP value of a poor solvent (unit: MPa 1 / 2 ) is shown. In the table, the "vapor pressure difference" column for "solvent" indicates the difference (unit: kPa) obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent. In the table, the "Q2 / V" column under "Discharge Conditions" indicates the ratio of the discharge amount Q2 (L / min) of the TAC solution discharged from the nozzle to the flow rate V (L / min) of the dry airflow flowing in the direction in which the TAC solution is discharged.

[0100] [Table 2]

[0101] As shown in Table 2, it was confirmed that the method for producing a hollow fiber according to the present invention makes it possible to easily produce a hollow fiber that contains triacetyl cellulose and has a smooth surface. In contrast, in Comparative Example B1, in which the volume ratio of the poor solvent content to the total volume of the good solvent and poor solvent was 10 volume % or less, the yield of hollow fibers with a smooth surface was less than 50%. This is presumably because the content of the poor solvent was too small, causing the good solvent to evaporate rapidly from the discharged liquid flow to form a TAC skin layer, and the skin layer to collapse due to the subsequent evaporation of the solvent, resulting in the formation of many hollow fibers with numerous wrinkles on the surface. In Comparative Examples B2 and B3, in which the volume ratio of the poor solvent content to the total volume of the good solvent and poor solvent was more than 30 volume %, the yield of hollow fibers with a smooth surface was also less than 50%. This is presumably because the content of the poor solvent was too high, which slowed down the evaporation rate of the solvent from the liquid flow and made the layer composed of TAC thick, making it difficult to form cavities of a predetermined size inside the fiber.

[0102] It was also confirmed that when the poor solvent contained NMP or DMF, the yield of hollow fibers having a smooth surface was further improved (comparison between Examples B1, B2 and B5). It was also confirmed that when the difference obtained by subtracting the saturated vapor pressure of the poor solvent from the saturated vapor pressure of the good solvent was 35 kPa or more, the yield of hollow fibers having a smooth surface was further improved (comparison between Examples B1, B2 and B5).

[0103] It was also confirmed that when the liquid flow diameter of the TAC solution discharged from the nozzle was 1000 μm or less, the yield of hollow fibers having a smooth surface was further improved (comparison between Examples B3 and B7). In addition, it was confirmed that when the ratio Q2 / V of the discharge amount Q2 (L / min) of the TAC solution discharged from the nozzle to the flow rate V (L / min) of the dry airflow flowing in the direction in which the TAC solution is discharged is 0.1 or less, the yield of hollow fibers with a smooth surface is further improved (comparison between Examples B4 and B6).

Claims

1. A step A1 of preparing a solution containing triacetyl cellulose, a good solvent, and a poor solvent, the volume ratio of the content of the poor solvent to the total content of the good solvent and the poor solvent being 5 to 30 volume %; A step A2 of spraying the solution to form hollow particles having an outer shell containing triacetyl cellulose, a difference obtained by subtracting the saturated vapor pressure of the poor solvent at 20° C. from the saturated vapor pressure of the good solvent at 20° C. is 23 kPa or more; the difference between the Hansen solubility parameter of the good solvent and the Hansen solubility parameter of the poor solvent is 15.0 MPa 1 / 2 or less; In the step A2, the solution is sprayed using a sprayer in a drying chamber in which a dry air stream heated to 40 to 250° C. flows, and the formed fine droplets are dried by the heated dry air stream to form the hollow particles. A method for producing hollow particles.

2. The difference obtained by subtracting the saturated vapor pressure of the poor solvent at 20 ° C from the saturated vapor pressure of the good solvent at 20 ° C is 34 kPa or more, the difference between the Hansen solubility parameter of the good solvent and the Hansen solubility parameter of the poor solvent is 11.4 MPa 1 / 2 or less; The temperature of the heated dry air stream is 100 to 200° C. The method for producing hollow particles according to claim 1 .

3. 3. The method for producing hollow particles according to claim 1, wherein a difference obtained by subtracting the saturated vapor pressure of the poor solvent at 20°C from the saturated vapor pressure of the good solvent at 20°C is 35 kPa or more.

4. The distance between the Hansen solubility parameter of the good solvent and the Hansen solubility parameter of the poor solvent is 11.3 MPa. 1/2 The method for producing hollow particles according to any one of claims 1 to 3, wherein the following is true:

5. The method for producing hollow particles according to any one of claims 1 to 4, wherein the good solvent comprises dichloromethane.

6. The method for producing hollow particles according to any one of claims 1 to 5, wherein the poor solvent comprises at least one selected from the group consisting of N-methyl-2-pyrrolidone and dimethylformamide.

7. 7. The method for producing hollow particles according to claim 1, wherein in the step A2, a ratio Q / V of a spray amount Q (L / min) of the solution sprayed in the step A2 to a flow rate V (L / min) of a dry airflow flowing in a direction in which the solution is sprayed is 0.1 or less.

8. The method for producing hollow particles according to any one of claims 1 to 7, wherein in the step A2, droplets formed by spraying the solution have a diameter of 1000 µm or less.

Citation Information

Patent Citations

  • Process for preparing porous cellulose beads

    JP1977129788A

  • Production of microcapsule of improved hydrophilic nature

    JP1980129145A

  • Sample extractor in cereal grain drier

    JP1985023773A

  • Cellulose acetate fiber, cellulose acetate tow band, and method for manufacturing cellulose acetate tow band

    JP2020007686A